2019
DOI: 10.3906/sag-1812-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cancer risk in patients with periodontal diseases

Abstract: In this study, we aimed to assess the cancer risk among patients with periodontal disease. Materials and methods: Patients diagnosed with periodontal diseases at Hacettepe University between 2007 and 2012 were included and data on the diagnosis of any cancer after periodontal disease were collected from patient files. The age-and sex-standardized incidence rates (SIRs) were calculated using Turkish National Cancer Registry 2013 data. Results: A total of 5199 patients were included. Median follow-up was 7.2 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Another study on 5,199 patients with 7 years of follow-up even demonstrated an increase in the risk of cancer to 17% in subjects with active periodontal diseases. Furthermore the risk of prostate cancer is significantly enhanced among men with periodontal diseases ( Guven et al., 2019 ). Increased levels of prostate specific antigen (PSA), a marker used for prostate cancer screening, were found in patients with chronic periodontal disease ( Lee et al., 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…Another study on 5,199 patients with 7 years of follow-up even demonstrated an increase in the risk of cancer to 17% in subjects with active periodontal diseases. Furthermore the risk of prostate cancer is significantly enhanced among men with periodontal diseases ( Guven et al., 2019 ). Increased levels of prostate specific antigen (PSA), a marker used for prostate cancer screening, were found in patients with chronic periodontal disease ( Lee et al., 2017b ).…”
Section: Discussionmentioning
confidence: 99%
“…Corbella et al (2018) reported a trend of increased cancer risk in patients with PDs but could not conclude because of the small number of studies [ 183 ]. Güven et al (2019) reported a negative association between PDs and cancers in an observational study, including 5199 patients [ 184 ]. With a follow-up of 7.2 years, patients with PDs had a 17% higher risk of cancer compared with those without PDs, for the same age groups and gender.…”
Section: Link Between Nutrition Periodontitis and Other Main Chromentioning
confidence: 99%
“…The risk of developing cancer rose to 17% in patients suffering from PD, and it was found that in patients with moderate or severe periodontitis, the risk of neoplastic tissues is higher than in patients with milder forms, although their risk is not negligible [ 41 ]. In a recent review from 2020, Nwizu et al pointed out a positive association between PD and cancer risk and hypothesized that, regarding PD, certain anatomic sites may be at higher risk for developing neoplasia, especially the esophagus and upper gastro-intestinal tract, which are adjacent to the oral cavity [ 42 ].…”
Section: Discussionmentioning
confidence: 99%